CLASSROOM COMMUNICATION IN THE ONLINE ENVIRONMENT - PERCEPTIONS AND DIRECTIONS OF ACTION - ȘTEFAN, Mihaela Aurelia; Popescu, Alexandrina Mihaela (Analele Universității din Craiova. Annales de l'Université de Craiova = Annals of the University of Craiova. Seria Psihologie, pedagogie, 2020)
Communication, a transfer of information between a sender and a receiver, as a result of which the information transmitted and received is understood and interpreted in the same way by the two parties involved, can be revisited from the perspective of the digital context.Classroom communication aims to produce changes, positive transformations in terms of knowledge, affectivity and behaviour, of the personality profile of the subjects. Based on this asumption, the following questions are outlined: How can the online communication process be optimised so that the message sent is clearly understood? What is the impact of the online environment on classroom communication?The current paper represents an investigative approach that aims to provide data on the students' perceptions of online communication-related issues and effects.